Advances in artificial intelligence applications for ocular surface diseases diagnosis - Ji, Yuke; Liu, Sha; Hong, Xiangqian; Lu, Yi; Wu, Xingyang; Li, Kunke; Li, Keran; Liu, Yunfang (Frontiers in Cell and Developmental Biology, 2022)
In recent years, with the rapid development of computer technology, the continual optimization of various learning algorithms and architectures, and the establishment of numerous large databases, artificial intelligence (AI) has been unprecedentedly developed and applied in the field of ophthalmology. In the past, ophthalmological AI research mainly focused on posterior segment diseases, such as diabetic retinopathy, retinopathy of prematurity, age-related macular degeneration, retinal vein occlusion, and glaucoma optic neuropathy. Meanwhile, an increasing number of studies have applied AI to the diagnosis of ocular surface diseases. In this review, we summarize the research progress of AI in the diagnosis of several ocular surface diseases, namely keratitis, keratoconus, dry eye, and pterygium. We discuss the limitations and challenges of AI in the diagnosis of ocular surface diseases, as well as prospects for the future.